Comprehension Level Analysis Self Student of SMAN 2 Tilatang Kamang - Fajri, Hayatunnisa; Ardi, Zadrian (Jurnal Aplikasi IPTEK Indonesia, 2021)
This research is motivated by field phenomena in schools where many students do not have self-understanding, most students do not understand their strengths and weaknesses, both in terms of interests, abilities , personality, and attitudes. This study uses a quantitative method with a descriptive approach. The population used in this study was 285 students enrolled in the 2022/2023 academic year with a sample of 166 people, who were selected using the simple random sampling technique. Collecting data in this study used a self-understanding questionnaire with a Likert scale model. The data was processed using descriptive statistical analysis techniques . The results showed that students' self-understanding at SMA Negeri 2 Tilatang Kamang was in the moderate category with a percentage of 59.09%. Based on the aspect of self-understanding categorized: (1) the aspect of interest is in the low category 38.6%, (2) the aspect of ability is in the high category 43.4%, (3) the personality aspect is in the medium category 48.2%, (4 ) the attitude aspect is in the high category, namely 45.8%. Based on the results of this study, it is expected that counseling teachers can provide assistance in the form of information services, individual counseling services, group guidance services.